Glioblastoma multiforme (GBM): An overview of current therapies and mechanisms of resistance. (September 2021) - Wu, Wei; Klockow, Jessica L.; Zhang, Michael; Lafortune, Famyrah; Chang, Edwin; Jin, Linchun; Wu, Yang; Daldrup-Link, Heike E.
Abstract: Glioblastoma multiforme (GBM) is a WHO grade IV glioma and the most common malignant, primary brain tumor with a 5-year survival of 7.2%. Its highly infiltrative nature, genetic heterogeneity, and protection by the blood brain barrier (BBB) have posed great treatment challenges. The standard treatment for GBMs is surgical resection followed by chemoradiotherapy. The robust DNA repair and self-renewing capabilities of glioblastoma cells and glioma initiating cells (GICs), respectively, promote resistance against all current treatment modalities. Thus, durable GBM management will require the invention of innovative treatment strategies. In this review, we will describe biological and molecular targets for GBM therapy, the current status of pharmacologic therapy, prominent mechanisms of resistance, and new treatment approaches. To date, medical imaging is primarily used to determine the location, size and macroscopic morphology of GBM before, during, and after therapy. In the future, molecular and cellular imaging approaches will more dynamically monitor the expression of molecular targets and/or immune responses in the tumor, thereby enabling more immediate adaptation of tumor-tailored, targeted therapies. Graphical Abstract: ga1